A longitudinal study of 340 young people with or without a visible difference: The impact of teasing on self-perceptions of appearance and depressive symptoms. (March 2016) - Feragen, Kristin Billaud; Stock, Nicola Marie
Highlights: Longitudinal changes in appearance satisfaction and depression were associated with teasing. The impact of teasing over time was greater for adolescent females than for males. Longitudinal changes were found irrespective of the presence of a visible difference. Positive social experiences may act as a buffer against incidences of teasing. Abstract: Previous research in both the general population and in those with a visible facial difference has identified potential associations between teasing, dissatisfaction with appearance and emotional distress. However, most studies are based on cross-sectional and retrospective methodology, restricting the interpretation of findings. The present study explored the longitudinal impact of perceived teasing on satisfaction with appearance and depressive symptoms in young people with and without a visible congenital condition. Routine psychological assessments were conducted at ages 10 and 16 years ( N = 340). Experiences of teasing after the age of 10 significantly impacted on appearance evaluations and depressive symptoms in adolescent females. The impact of teasing on adolescent males was possibly counteracted by reports of more positive social experiences. Early identification of perceived teasing in all children to prevent the development of emotional problems and dissatisfaction with appearance is of vital importance.